The impact of the components of the accounting information system on the protection of e-commerce operations of banks operating in Sudan - Othman, Mohieddin Mohamed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to explain the impact of accounting information system components on the commercial banks in Sudan - to protect e- commerce operations. To achieve this objective, the analytical descriptive approach of the selected study sample has dependable, the respondents are employees of the Departments of Technology and financial management in Sudanese Banks, the problem of study is the difficulties facing accounting information systems under the use of e- commerce, and the procedures to be taken to protect e- commerce operations.The results of the study showed that, the accounting information system components is effective to protect e- commerce operations in the commercial banks in Sudan, beside the provision of an effective system of accounting for costs and financial accounting helps control the electronic activities of banks. Based on the findings, the study recommends that, the necessity of verifying the validity of the data during the entering of the accounting information system, also the auditor's report should not be to traditional and formal aspects only, nearby the attention to the requirements of electronic commerce as required by the environmental and professional renewable conditions of the profession of accounting and auditing, besides the validate and authenticity website of the Banks.
Keywords: information system; protection; e-commerce; banks; Sudan